Identifying care problem clusters and core care problems of older adults with dementia for caregivers: a network analysis - Leng, Minmin; Han, Shuyu; Sun, Yue; Zhu, Zheng; Zhao, Yajie; Zhang, Yizhu; Yang, Xianxia; Wang, Zhiwen (Frontiers in Public Health, 2023)
Background: A shift in research interest from separate care problem to care problem clusters among caregivers of people living with dementia may contribute to a better understanding of dementia care.However, the care problems network among caregivers of people living with dementia are still unknown. This study aimed to identify care problem clusters and core care problems, and explore demographic variables associated with these care problem clusters among caregivers of people living with dementia. Methods: Participants were recruited through memory clinics and WeChat groups. The principal component analysis was applied to identify care problem clusters. The network analysis was conducted to describe the relationships among care problems and clusters. Multiple linear models were used to Clusters of Dementia Care Problems 2 explore the associated factors for the occurrence of the overall care problems and top three central care problem clusters.Results: A total of 1012 carer-patient pairs were included in the analysis. Nine care problem clusters were identified. In the entire care problem network, ''deterioration in activities of daily living'' was the most core care problem cluster across the three centrality indices, followed by ''verbal and nonverbal aggression'' and ''loss of activities of daily living''. Variables including marital status, years of dementia diagnosis, number of dementia medication type, and caregiver's educational attainment were associated with the prevalence of these three care problem clusters.Our study suggests that there is a need to evaluate care problem clusters for the improvement of care problem management among people living with dementia. It is particularly important to include assessment and treatment of core care problem as an essential component of the dementia care.